Migrazioni virtuali: teletandem per l’apprendimento di una L2 - Leone, Paola (Incontri. Rivista europea di studi italiani, 2017)
Virtual migrations. Teletandem for second language learningTeletandem is included as an L2 learning context in different university degree courses throughout the world. It is a form of telecollaboration by which two students, proficient in two different languages, interact orally via Voice Over Internet Protocol (VOIP) technology in order to develop their L2 competences. The current paper aims to describe a learning scenario based on teletandem as it is designed and experienced at the University of Salento. Together with teletandem sessions, the learning scenario includes different classroom tasks, performed collaboratively by students and teachers. For the tasks, video recordings of teletandem sessions are used. Students are asked to select parts of the conversation with their partner in order to discuss linguistic and cultural communicative problems. The whole learning scenario aims primarily to enhance students’ oral communication abilities (both in monologues and in interaction). The following topics are therefore discussed: the basic characteristics of teletandem interaction; digital resources used for the learning scenario; the role of the teacher as a mediator; and how mediation sessions are organized.